2013
DOI: 10.1136/acupmed-2012-010268
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Skin Surface Temperature at An Acupuncture Point with Moxibustion

Abstract: ObjectiveThis study evaluates the thermographic changes associated with moxa burner moxibustion at the SP6 acupuncture point to establish an appropriate, safe distance of efficacy for moxibustion.MethodsBaseline temperature changes using a moxa burner were obtained for a paper substrate at various distances and times, and the tested with volunteers in a pilot study. A single-group trial was then conducted with 36 healthy women to monitor temperature changes on the body surface at the acupuncture point (SP6).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Some have observed the impact of moxibustion at different distances on local skin temperature. The safe distance for indirect moxibustion seems to be 3-4 cm [ 35 , 36 ]. The temperature of burning moxa can play a therapeutic role, but it offers a risk of burns if administered improperly.…”
Section: Discussionmentioning
confidence: 99%
“…Some have observed the impact of moxibustion at different distances on local skin temperature. The safe distance for indirect moxibustion seems to be 3-4 cm [ 35 , 36 ]. The temperature of burning moxa can play a therapeutic role, but it offers a risk of burns if administered improperly.…”
Section: Discussionmentioning
confidence: 99%
“…Moxibustion at CV4 can regulate San Jiao, warm and invigorate kidney qi, and promote bladder gasification to improve urination and defecation. Wormwood [ 9 ] belongs to the feverfew family of plants and is bitter in flavor, warm in nature, and fragrant in odor. It is flammable and produces moderate heat when burned.…”
Section: Discussionmentioning
confidence: 99%
“…e authors observed that there was significant increase in temperature at a region of interest (ROI) around the Dazhui (GV14) acupoint. Lin et al [6] used IRT to monitor skin temperature changes of human body in 36 healthy female subjects at acupoints during moxibustion and discovered that the maximum temperature increased by 11°C at the SP6 acupoint. With the application of IRT, Raith et al [7] studied the rising phenomenon of skin temperature at Hegu (LI4) during laser acupuncture therapy.…”
Section: Introductionmentioning
confidence: 99%